Effect of Trade Openness and Agriculture on Tax Revenue Performance in Kenya - Moses , Jordan; Obange , Nelson; Kiganda, Evans (International Journal of Economics, 2023)
Purpose: Taxes play a critical role for most governments around the world in funding investments in capital, infrastructure and the delivery of essential services. The study therefore sought to examine the effect of trade openness and agriculture on tax revenue performance in Kenya. Methodology: The study adopted correlational research design, Vector Error Correction Model (VECM) mechanism and Granger causality test to establish the relationship between the study variables. The choice of the VECM was influenced by its ability to estimate both short run and long run relationships. The theoretical framework of the study followed Heller's neoclassical maximization utility approach. Annual time series data for the study were sourced from the World Bank Development Indicators for the period 1980-2020. Results: The study findings established that in the long-run agriculture share (-0.64, t-statistics = 14.57) and trade openness (-0.08, t-statistics = 3.88) have negative and significant effect on tax revenue performance in Kenya. The Pairwise Granger Causality test results indicated unidirectional causality running from tax revenue performance to trade openness. This suggests that tax rates have effect on trade openness in Kenya. Unique Contribution to Theory, Policy and Practice: The study adds to literature by proving the Arthur's Laffer curve theory which advocates for lowering tax rates in order to boost productivity and encourage expansion of corporation. The findings of the study may provide the National Treasury with foundation for policy formulation and analytical framework for estimating the associated tax revenue with variables under consideration in this study. The study may be of importance to KRA in determining appropriate tax rates that are favorable in boosting revenue mobilization.